RANCANG BANGUN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB PADA CV ABU HERBAL - Fatahillah Dian Pratomo (2023)
CV Abu Herbal is a company engaged in the field of food ingredients where this food ingredient is honey. This company has a production site in Gunung Putri, Bogor. Until now, CV Abu Herbal itself still uses a manual attendance system which is done only by memorizing the faces of employees who have come without any records. This manual attendance system is of course widely used by employees who are less responsible, such as being present at hours that are not in accordance with company regulations and irregular coming and going, this is something that is detrimental to CV Abu Herbal. Therefore, CV Abu Herbal wants to have an attendance system through the website so that employees cannot attend and go home freely without any regulations and can follow the company's working hours regulations. The author will create a web-based attendance system. This attendance system can also be used to recapitulate the number of employee attendance in a one-month period for each employee and apply for leave. This system will be developed with a website display so that it will make it easier for the admin to manage the existing system.